Performance of sweet passion fruit seeds submitted to pre-germination treatments - Fávaris, Nathália Aparecida Bragança; Lopes, José Carlos; Freitas, Allan Rocha de; Cabanez, Patrícia Alvarez; Alexandre, Rodrigo Sobreira (Scientia Plena, 2020)
Brazil is the world's largest consumer and producer of passion fruit (Passiflora spp.). Its fruit is widely accepted by consumers mainly in terms of natura consumption, juices, and medicines. However, these plants are spread mainly via seminiferous propagation, in which low and uneven seed germination is verified. The objective of this work was to study seed performance and initial growth of Passiflora alata Curtis seedlings as a function of pre-germination treatments. Seeds of P. alata extracted from mature fruits harvested were used and manually extracted from the fruits, and the aryl was removed by rubbing in a stainless steel mesh sieve with quicklime, followed by drying in the shade on filter paper for 24 hours. The seeds were submitted to physical scarification and immersed in distilled water for 0; 24; 48; 72; 96; and 120 hours of stirring. The seed scarification method by cracking interferes negatively in the germination and initial growth of P. alata seedlings. Intact seeds had a higher percentage of germination as the stirring time of the seeds imbibed in water increased. The cracked seed treatment provided the highest averages when electrical conductivity was evaluated in the stirring time of 120 hours. Intact seeds immersed in distilled water with stirring for 120 hours provide greater germination and initial growth of P. alata Curtis seedlings.